Apoio Institucional : dispositivo para mudança de práticas e fortalecimento das redes de atenção em saúde - Braga, Denise Aparecida (2017)
SUS (Portuguese acronym for Unique Health System) is a political and organizational formulation for the reorganization of health services and actions, guided by the principles of universality, equity and integrality, but since its creation, it has faced major challenges for its effective consolidation and implementation. In order to meet the health needs of the population, services must be organized in a network based on Basic Attention to access levels of greater complexity. In the search for favorable transformations for the qualification of care, institutional support emerges as a device capable of strengthening the spaces of attention, aiming to modify the forms of health planning and management. The support arises through the need to review the processes of production of care, with the valuation of the subjects involved and the achievement of more democratic ways of doing health. Thus, the present study sought to analyze the practices of institutional support as a device for strengthening health care networks, based on the perceptions of supporters and workers considering the potentialities, challenges and strategies used in the support function. The research was drawn from a qualitative approach, in the form of an exploratory-descriptive case study. For this, the focal group technique was used with supporters as well as workers of supported team who met the selection criteria. Thematic categorical content analysis technique was used for the systematization of the material produced. The research findings point to the need to bond the supporters with the teams to be supported, as well as an adequate time for insertion into the routine of services, to produce organized collectives aimed at new forms of work management. They also indicate the need for appropriation of strategies and tools for the support function, however, in addition to those established in the literature, others can be constructed in the act, in the practice of actions. Moreover, they point out challenges that must be considered and put into analysis, especially those related to hegemonic and vertical managerial issues, in search of transformations of management and attention practices in a proposal to foster co-management, to promote the production of collectives and the autonomy of the subjects Involved with health care.